Histomorphology of the lesions of the umbilicus: Are we naïve about the navel? - Saranya Singaravel; Poonam C Yadav (Indian Journal of Pathology and Microbiology, 2021)
Context: Twelve-year retrospective study of surgically excised umbilical lesions received for histopathology in a pediatric tertiary care hospital. Aims: To study histopathology of the umbilical lesions and review pertinent literature on the embryological basis of these lesions. Subjects and Methods: We reviewed cases of umbilical lesions and classified them as “developmental” and “others.” Developmental cases were sub-classified based on the mechanism as those due to defect in the closure of body wall, defect in the closure of the umbilical ring, persistence of embryonic remnants, or failure of epithelization. Persistent embryonic remnants were subdivided into fistula, sinus, and cyst. Histology of all the cases was studied and the different types of tissue in omphalomesenteric ducts (OMD) remnants were identified. Statistical Analysis Used: Descriptive statistics were used as required. Results: Seventy-one cases in the age range of 1 day to 13 years were studied and male preponderance was noted. The developmental lesions included 4 omphalocele sacs with dense acute inflammation, 2 umbilical hernial sacs with fibrocollagenous tissue, 30 OMD remnants, 10 allantoic duct remnants, 19 umbilical granulomas, and 2 cases showing more than one developmental mechanism. Four cases were classified as “others” including 3 epidermal inclusion cysts and 1 skin tag. Among OMD remnants, sinuses (arising from the distal tract) were found to be the most common. Histological examination of the OMD remnants showed enteric (18), enteric and gastric (5), colonic (4), enteric and colonic (2), and pancreatic and enteric and gastric mucosae (1). Conclusion: Accurate diagnosis is essential for definite treatment of these lesions.